Terrorism and disaster new threats, new ideas - Clarke, Lee Ben. (Amsterdam ; Boston : Elsevier/JAI, 2003)
The terror attacks of 9.11 signalled that people are increasingly put at risk of not only terrorism but natural and technological disasters as well. Since 9.11 scholars have been asking new questions about catastrophe and made important and interesting innovations in methods, concepts, and theories regarding disaster and terror. This volume brings together a creative set of papers, most of which are about the 9.11 attacks. They draw from several disciplines to address key questions: what lessons does the response to the collapse of the World Trade Center have for disaster planning? what has 9.11 meant for civil liberties in the US? how will survivors react over the long run? and how do we conceptualize panic and mass response?
Introduction: 9.11 as disaster: on worst cases, terrorism, and catastrophe / Lee Clarke -- A civil defense against terror / Orlando Rodriguez -- Empire of fear: imagined community and the September 11 attacks / Ann Larabee -- Disaster beliefs and institutional interests: recycling disaster myths in the aftermath of 9--11 / Kathleen Tierney -- The fox and the hedgehog: myopia about homeland security in U.S. policies / James K. Mitchell -- Terrorism as disaster: selected commonalities and long--term recovery for 9/11 survivors / Brent K. Marshall, J. Steven Picou and Duane A. Gill -- Reconsidering convergence and converger legitimacy in response to the World Trade Center disaster / James M. Kendra and Tricia Wachtendorf -- Conceptualizing responses to extreme events: the problem of panic and failing gracefully / Lee Clarke.
Includes bibliographical references.
Description based on print version record.
Keywords: September 11 Terrorist Attacks, 2001 -- Psychological aspects; Terrorism -- Psychological aspects; Disasters -- Psychological aspects; Terrorism -- United States -- Prevention; Terrorist attack; Social impact of disasters; Political Science -- Political Freedom & Security -- Terrorism